The Sogdian epitaph of Shi Jun and his wife. (22nd October 2021) - Sims-Williams, Nicholas
Abstract: Three bilingual Chinese and Sogdian epitaphs have been discovered and published in recent years. The first of these forms part of the tomb of Wirkakk, alias Shi Jun 史君 "Mr Shi", and his wife Wiyusi, who were buried in 580 ce in Chang'an, the capital of the Northern Zhou. This article provides some corrections to the previous editions of the Sogdian version and attempts to elucidate points which have so far appeared obscure.